Narrarsi attraverso: il nome proprio in autobiografia - Immacolata Messuri; Lara Balleri (Studi sulla Formazione)
The autobiographical method is used in the pedagogical field to allow the person to access experiences, read the present and guide future choices. Among the languages that lend themselves to this, the autobiographical narration, in particular, is capable of making significant the selection that the narrated story makes of lived experiences. The name serves as a privileged filter of autobiographical access to the self, between mimesis and metamorphosis. The contribution will describe how this is possible.